Carbon flux variation and associated biomass energy storage economic value implications in the Dinghushan Biosphere Reserve. (20th November 2022) - Njoroge, Brian; Li, Yuelin; Liu, Juxiu; Otieno, Dennis; Li, Runzhou; Yu, Mengxiao; Chen, Zhi; Meng, Ze; Tenhunen, John
Abstract: Subtropical forests are a major carbon (C) storage pool and are therefore rich in biomass energy reservoirs. However, there have been no studies that quantify the C storage economic value, especially in the region of the Dinghushan Biosphere Reserve. This study is the first attempt to apply the eddy covariance technique to measure biomass energy storage and the associated economic value and demonstrates that CO2 flux measurement is a viable method for quantifying the ecosystem biomass energy storage. CO2 flux and micro-meteorological data were collected and analyzed to calculate the daily C sequestration and establish their inter-relationship. In addition, we used the C price estimates of Guangdong Province in China to determine the capital value of the C sequestered. The measured average annual precipitation was 1459.4 mm, the average temperature was 22.9 °C and the highest photosynthetic photon flux density (PPFD) was 334.92 μmol m −2 s −1 . CO2 flux and biomass energy storage varied seasonally. Photosynthetic photon flux density (PPFD) was highly correlated with gross primary production (GPP) ( r 2  = 0.99, p  < 0.0001). Soil temperature was correlated with net ecosystem exchange (NEE) ( r 2  = 0.84, p  < 0.0001). There was a positive correlation (r 2  = 0.49, p < 0.0001) between soil moisture and NEE. The Dinghushan Biosphere Reserve sequestered an average of 5300 tCy −1 equivalent to RMB 3.3 million (USD 530, 000). We conclude that economically, the Dinghushan Biosphere Reserve is highly significant to China's Guangdong Province because of its rich biomass energy reserves via C sequestration and our findings will stimulate the formulation of more aggressive conservation policies that will inevitably lead to better management of the reserve. Graphical abstract: Image 1 Highlights: Subtropical forests are major carbon storage pools and therefore reservoirs of biomass energy. Using CO2 flux data we quantified the biomass energy storage and the economic value of C sequestration. Micro-meteorological conditions had a strong correlation with CO2 flux. We measured a sequestration average of 5300 tC y −1 equivalent to RMB 3.3 million (USD 530, 000).